Effect of various metal ions on gypsum precipitation - SAYAN, PERVİZ (TAYLOR & FRANCIS LTD, 2021)
The effect of various metal ions, namely Mn2+, Al3+, Pb2+, Cr3+, and Zn2+, on the precipitation of gypsum was investigated in the present study. The structure, functional groups, morphology, and size of gypsum crystals precipitated with additives using the batch method were evaluated experimentally through X-ray diffraction (XRD), Raman spectroscopy, thermogravimetric analysis (TGA)-Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and particle size and morphological analysis. The results indicate that Pb2+ and Zn2+ ions, in particular, exerted significant effects on gypsum precipitation. When Al3+ ions were the additive, only needle-like gypsum formed, whereas compact plate-like gypsum was observed in the presence of Pb2+ ions. The addition of Zn2+ ions resulted in gypsum particles of larger sizes with agglomerated shapes, simultaneously achieving an increased filtration rate of the suspensions from 5.88x10(-7)-2.44 x 10(-6) m(3)/s. A detailed analysis of the crystal shape showed that while the elongation values decreased, the circularity values increased as compared with the gypsum precipitated in pure medium. These results show how metal ions can be used to effectively modify gypsum size, shape, and crystal morphology.
Keywords: Gypsum; metal ion; morphology; precipitation; shape parameters; CALCIUM-SULFATE DIHYDRATE; CRYSTALLIZATION; HEMIHYDRATE